H-v drawings of binary trees - Sung Kwon Kim (Software Visualization, 1996)
This chapter considers h-v drawings of binary trees and presents new results on it. We prove that binary trees with n nodes can be h-v drawn so that the total edge length is O(n log log n), and so that the maximum edge length is O(SQRT(n log n).